FAKTOR KEBERADAAN BREEDING PLACE DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI SEMARANG - Prasti Widyorini; Nur Endah Wahyuningsih; Retno Murwani (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
At the present, the Dengue Hemorrhagic Fever (DHF) is one of health problem In Indonesia. Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted through the bite of Aedes aegypti mosquito. Spreading of DHF influenced environmental factors. The purpose of this research is to determine the relationship between environmental factors with incidence of DHF in Semarang Hospital, Tugurejo Hospital, Kariadi Hospital, and Tlogorejo Hospital. This research was observational analitical research with case control approach. The sample (case) was all patiens with DHF that recorded in those hospitals between March to May 2016 (40 cases), and the sample of (control) was the people around the patient who do not suffered DHF with radius of 100 meters, wich equated ages and education (40 respondents). The dependent variable was incidence of DHF and the independent variable was breeding place. These data analyzed by Chi Square test. The results show that there are relationship between breeding place (p = 0,048) with incidence of DHF. The breeding place has relationship with incidence of DHF.